Factors influencing Chinese young adults' intention to receive HPV vaccination: the mediating role of attitude - Hongyan Wu; Guateng Liow; Zhengxi Zhou; Jifeng Li (Frontiers in Public Health)
IntroductionThis study examines the intention of young adults to receive the Human Papillomavirus vaccination in China, with a specific focus on the mediating role of attitude within an integrated framework of the Health Belief Model and the Theory of Planned Behavior.MethodsA convenience sampling method was utilized to collect data through an online questionnaire targeting young adults aged 18 to 26. The data were analyzed using Partial Least Squares Structural Equation modeling to explore the relationships between various factors affecting vaccination intention.ResultsThe findings revealed that perceived susceptibility, perceived severity and perceived benefits have significant positive effects on attitudes toward the HPV vaccine. Subjective norms, attitude and perceived behavioral control positively influence the intention to receive the HPV vaccination. Attitude was identified as a significant mediator between these variables and intention to receive HPV vaccination.DiscussionThis study highlights the need for targeted educational campaigns to improve young adults' HPV vaccine attitudes. Public health initiatives may potentially increase HPV vaccination rates.